2021
DOI: 10.1167/iovs.62.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Integration of Perceptually Suppressed Visual Information in Amblyopia

Abstract: Purpose The purpose of this study was to assess whether motion information from suppressed amblyopic eyes can influence visual perception. Methods Participants with normal vision ( n = 20) and with amblyopia ( n = 20; 11 anisometropic and 9 strabismic/mixed) viewed dichoptic, orthogonal drifting gratings through a mirror stereoscope. Participants continuously reported form and motion percepts as gratings rivaled for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 112 publications
0
7
0
Order By: Relevance
“…Studies show that patients thought to be treated effectively, achieving normal VA, still exhibit significant impairment in contrast sensitivity and stereoacuity [62]. As already mentioned, the visual information from the amblyopic eye, though being suppressed, is still available for visual processing, contributing to binocular vision [18]. These observations suggest that amblyopia treatment should address the binocular dysfunction [13].…”
Section: Binocular Approachesmentioning
confidence: 89%
See 2 more Smart Citations
“…Studies show that patients thought to be treated effectively, achieving normal VA, still exhibit significant impairment in contrast sensitivity and stereoacuity [62]. As already mentioned, the visual information from the amblyopic eye, though being suppressed, is still available for visual processing, contributing to binocular vision [18]. These observations suggest that amblyopia treatment should address the binocular dysfunction [13].…”
Section: Binocular Approachesmentioning
confidence: 89%
“…Suppression is marked across the whole amblyopic visual field, but it is stronger in the foveal region, creating a distinct functionally blind area called suppression scotoma [14,18,19]. Luminance and contrast sensitivity thresholds are elevated within that area, form and motion information are suppressed, and objects presented within the scotoma do not become consciously aware [14,18,19]. Recent studies show that the information from the amblyopic eye, though strongly suppressed from conscious perception, still remains available for binocular processing [18].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…But recent studies showed that visual information seen by the amblyopic eye, which is under suppression, can be binocularly integrated and influence the overall visual percept. According to the authors, visual information subjected to interocular suppression can still contribute to binocular vision and suggest an appropriate optical correction for the amblyopic eye to improve image quality for the binocular combination [37]. It means that suppressed visual information continues to be represented within the brain even when it is blocked by chronic pathological suppression.…”
Section: Joj Ophthalmologymentioning
confidence: 99%
“…Amblyopia is a common eye disease in children associated with impairments in processing tactile, motion, and visual stimuli, resulting in abnormal visual development, low visual acuity, and binocular diplopia (1)(2)(3). Amblyopia was once considered a monocular disease; however, a growing body of evidence suggests the involvement of structural and functional abnormalities in both eyes (4). Pediatric amblyopia is associated with high financial and psychological burden to both children and parents.…”
Section: Introductionmentioning
confidence: 99%